1979
DOI: 10.1254/jjp.29.161
|View full text |Cite
|
Sign up to set email alerts
|

ROLE OF BRAIN AMINES IN THE FATAL HYPERPYREXIA CAUSED BY TRANYLCYPROMINE IN LiCl-PRETREATED RATS

Abstract: Tranylcypromine (TCP), a monoamine oxidase inhibitor, caused a fatal hyperpyrexia in rats pretreated with LiCl once a day for 4 days. Pretreatment with LiC1 alone did not alter the level of serotonin (5-HT). dopamine (DA) and norepin ephrine (NE) in the brain.In the fatal hyperpyrexia caused by LiCI plus TCP, the brain 5-HT and DA levels 'sere increased, whereas the brain NE level was decreased.Reserpine and a-methyl-p-tyrosine completely prevented the hyperpyrexia, but FLA-63 did not show any effect.The hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Serotonin receptor blockers, cyproheptadine and methysergide, did not prevent the hyper pyrexia as shown in our previous study (1). These results indicate that the hyperpyrexia induced by LiCI plus TCP depends specifically on the central DA mechanism.…”
Section: Effects Of Drugs On the Rectal Temperature In Intact Ratssupporting
confidence: 49%
See 1 more Smart Citation
“…Serotonin receptor blockers, cyproheptadine and methysergide, did not prevent the hyper pyrexia as shown in our previous study (1). These results indicate that the hyperpyrexia induced by LiCI plus TCP depends specifically on the central DA mechanism.…”
Section: Effects Of Drugs On the Rectal Temperature In Intact Ratssupporting
confidence: 49%
“…In a previous study (1), we demonstrated that tranylcypromine (TCP) produced a fatal hyperpyrexia in rats pretreated with repeated doses of LiCI. In the hyperpyrexia produced by LiCI plus TCP, the brain dopamine (DA) was postulated to play an essential role, because the occurrence of the hyperpyrexia was dependent upon the presence of the brain DA and was suppressed almost completely by DA receptor blocking drugs.…”
mentioning
confidence: 99%
“…In one series of experiments, rats were given a drug or an alkali metal once daily for 4 days. Control animals were given LiCI at a dose of 250 mg/kg which was used in our previous experiments (1,2). The alkali metals other than LiCI were given in two doses which were equivalent to that of LiCI either on the weight or molar basis.…”
mentioning
confidence: 99%
“…Our previous studies have shown that the dopamine (DA) in the caudate nucleus plays an important role in hyperpyrexia (1,2), as the occurrence of the hyperpyrexia was dependent on an increase in the brain DA and was suppressed by DA blockers. TCP increased the DA in the caudate nucleus, while pargyline was without effect (4).…”
mentioning
confidence: 99%